Implementation of the MSME Digitalization Policy Through the Markaz Application in Wonosobo Regency: Implementasi Kebijakan Digitalisasi UMKM melalui Aplikasi “Markaz UMKM” di Kabupaten Wonosobo - Anindita Sarsabila; Bachtiar Dwi Kurniawan (Universitas Indo Global Mandiri, 2026)
Purpose – This study aims to identify the factors influencing the implementation process of digitalization policy through the